Coagulation Profile Alterations in Patients with Alcoholic Liver Disease: A Study of Clinical and Diagnostic Implications - Srinivas KP, Gautam; Ramalingam, Anurada; Suresh A, Suresh A; Malaiyan, Jeevan (Journal of Neonatal Surgery, 2025)
Alcoholic liver disease (ALD) is a significant global health concern characterized by progressive liver damage, leading to coagulopathy and increased risks of bleeding and thrombosis. Understanding alterations in coagulation profiles, especially in the presence of comorbidities such as viral cirrhosis, is crucial for improving diagnostic and therapeutic strategies. This study aims to evaluate the coagulation profile in ALD patients, incorporating microbial and viral parameters for a comprehensive assessment. A prospective study was conducted on 120 patients diagnosed with ALD, including cases of alcoholic fatty liver, acute alcoholic hepatitis, and alcoholic cirrhosis. Clinical assessments, liver function tests, coagulation profiles, and microbial evaluations (viral hepatitis markers, gut microbiome analysis) were performed. Prothrombin time (PT), activated partial thromboplastin time (aPTT), and platelet counts were assessed alongside inflammatory markers such as IL-6 and TNF-α. Data were statistically analyzed using SPSS. Prolonged PT and aPTT were observed in 70% of cirrhosis cases, with thrombocytopenia noted in 80%. Viral co-infections significantly worsened coagulation parameters (p < 0.01), with elevated inflammatory markers correlating with disease severity. Gut dysbiosis was prominent in cirrhosis, characterized by reduced beneficial bacteria and increased pathogenic species. ALD results in significant coagulation abnormalities, exacerbated by viral cirrhosis and microbial dysbiosis. Incorporating microbial and inflammatory markers into routine assessments can enhance diagnostic accuracy and inform targeted therapeutic strategies.